UJI AKTIVITAS ANTIOKSIDAN DAN TOTAL FLAVONOID PADA EKTRAK ETANOL PINANG YAKI (Areca vestiaria) - Samosir, Ary Pratama; Runtuwene, Max Revolta John; Citraningtyas, Gayatri (UNIVERSITAS SAM RATULANGI, 2012)
This study aims to determine the antioxidant activity of the ethanol extract in fresh Pinang Yaki(Areca vestiaria) seeds and the total content of flavonoid compounds. Total Antioxidant test usedFerric Reducing Antioxidant Power (FRAP) method and Chang method, 2002, for calculate thetotal flavonoids and for test the antioxidant activity. Result from this study showed that theantioxidant activity of fresh samples is 3.80375 mmol/100g and the total flavonoids in freshsamples is 7.2374 mg / kg.Keywords : fresh samples of Pinang Yaki (Areca vestiaria), Antioxidant, total flavonoids, FerricReducing Antioxidant Power (FRAP)